2016
DOI: 10.24275/uam/izt/dcbs/hidro/2016v26n1/barriga
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific karyotypic variation in the silverside fish Chirostoma humboldtianum (Atheriniformes: Atherinopsidae)

Abstract: Within its genus, Chirostoma humboldtianum is one of the species with the widest distribution, inhabiting lake and pond environments along the Lerma-Santiago basin in the Mexican Plateau. Although the species is of great ichthyological, economic, and cultural relevance, factors related to human activity such as habitat loss, pollution, overfishing, and introduction of non-native fish have played important roles in the decline and disappearance of populations. With the aim of describing the karyotype of the spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
(25 reference statements)
2
0
0
Order By: Relevance
“…Likewise, decrease in observed heterozygosity suggests nonrandom mating and genetic drift (Loew et al, 2005), due that genetic drift causes random fixation and loss of alleles within population. In contrast, heterozygote excess appears to be due to the presence of hybrids within the sample (Pitchar et al, 2007) as has been earlier suggested for species of the genus (Barriga-Sosa et al, 2001). Translocations among populations and hybridization have been reported for this and others species of the genus (Alaye, 1996;Barriga-Sosa et al, 2001), however, this issues needs to be punctually addressed in further studies.…”
Section: Research Notesupporting
confidence: 50%
See 1 more Smart Citation
“…Likewise, decrease in observed heterozygosity suggests nonrandom mating and genetic drift (Loew et al, 2005), due that genetic drift causes random fixation and loss of alleles within population. In contrast, heterozygote excess appears to be due to the presence of hybrids within the sample (Pitchar et al, 2007) as has been earlier suggested for species of the genus (Barriga-Sosa et al, 2001). Translocations among populations and hybridization have been reported for this and others species of the genus (Alaye, 1996;Barriga-Sosa et al, 2001), however, this issues needs to be punctually addressed in further studies.…”
Section: Research Notesupporting
confidence: 50%
“…In contrast, heterozygote excess appears to be due to the presence of hybrids within the sample (Pitchar et al, 2007) as has been earlier suggested for species of the genus (Barriga-Sosa et al, 2001). Translocations among populations and hybridization have been reported for this and others species of the genus (Alaye, 1996;Barriga-Sosa et al, 2001), however, this issues needs to be punctually addressed in further studies. These 8 microsatellite loci are the first developed for C. humboldtianum and will be useful in investigating population genetics, conservation, and management of this and closely related species.…”
Section: Research Notesupporting
confidence: 50%